2002
DOI: 10.1007/s10071-002-0134-y
|View full text |Cite
|
Sign up to set email alerts
|

Rats use a sense of direction to alternate on T-mazes located in adjacent rooms

Abstract: Lister hooded rats were trained on a forced-sample T-maze alternation task in an environment lacking spatial landmarks. An early study of spontaneous alternation on the T-maze had shown that rats use a "spatial sense" to select alternate maze arms across mazes. As this phenomenon may provide a useful tool for studying the neural substrates of a directional sense, we wished to confirm this finding on a different version of the T-maze task, with well-trained animals. We found that rats successfully selected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
6
37
0
Order By: Relevance
“…After a variety of manipulations the author concluded that rats 'have a sense of direction or position in space' (p. 171) that can be used to remember which arm of the T has been most recently sampled. Recent data [30] has supported this conclusion.…”
Section: Delayed Alternationmentioning
confidence: 68%
“…After a variety of manipulations the author concluded that rats 'have a sense of direction or position in space' (p. 171) that can be used to remember which arm of the T has been most recently sampled. Recent data [30] has supported this conclusion.…”
Section: Delayed Alternationmentioning
confidence: 68%
“…For example, it has been reported that place learning tends to dominate choices early in training, whereas response learning dominates later in training (Packard and McGaugh 1996;Colombo et al 2003). Rats in the current study may also have relied on a nonegocentric or nonresponse-related strategy to solve this DMS version of the task, such as a sense of room direction, despite the testing being carried out in the dark (Dudchenko and Davidson 2002). For example, during the choice phase they may simply have used intramaze cues to avoid the sample arm that they had most recently exited, despite every attempt to wipe the floor and walls clean after the sample phase, or learned to choose the same direction to that from which they had recently come during the sample phase.…”
Section: Discussionmentioning
confidence: 84%
“…There are special cases in which local apparatus cues can control the head direction cells. Head direction cells can be controlled by changes in the orientation of an open behavioral apparatus when the apparatus is directionally polarized (e.g., a T-maze) and when there are no salient distal cues (50). If the geometry of an enclosed apparatus is strongly polarized, then the geometry can control the head direction cells even in the presence of distal cues (30).…”
Section: Neurophysiology Of Representations Of Placementioning
confidence: 99%